“Leopard skin sign”: the use of narrow-band imaging with magnification endoscopy in celiac disease - Tchekmedyian, Asadur J. (2017)
Celiac disease (CD) is an immune reaction to gluten containing foods such as rye, wheat and barley. This condition affects individuals with a genetic predisposition; it targets the small bowel and may cause symptoms including diarrhea, malabsorption, weight loss, abdominal pain and bloating. The diagnosis is made by serologic testing of celiac-specific antibodies and confirmed by histology. Certain endoscopic characteristics, such as scalloping, reduction in the number of folds, mosaic-pattern mucosa or nodular mucosa, are suggestive of CD and can be visualized under white light endoscopy. Due to its low sensitivity, endoscopy alone is not recommended to diagnose CD; however, enhanced visual identification of suspected mucosal abnormalities through the use of new technologies, such as narrow band imaging with magnification (NBI-ME), could assist in targeting biopsies and thereby increasing the sensitivity of endoscopy. This is a case series of seven patients with serologic and histologic diagnoses of CD who underwent upper endoscopies with NBI-ME imaging technology as part of their CD evaluation. By employing this imaging technology, we could identify patchy atrophy sites in a mosaic pattern, with flattened villi and alteration of the central capillaries of the duodenal mucosa. We refer to this epithelial pattern as “Leopard Skin Sign”. Since epithelial lesions are easily seen using NBI-ME, we found it beneficial for identifying and targeting biopsy sites. Larger prospective studies are warranted to confirm our findings.